Pharmacovigilance and Adverse Drug Reactions Reporting Process in West-Bank, Palestine - Anan Jarab; Hussein Hallak; Maher Khdour; Mohammad Dweib; Nima Yaghmour; Qusai Al-Shahed (My University, 2016)
Active national pharmacovigilance programmes are needed to monitor adverse drug reaction (ADR) data in local populations. The objective of this study was to describe the knowledge, experiences, attitudes and perceived barriers to reporting of suspected ADRs by community and hospital pharmacists in West Bank, Palestine. Between December 2014 and March 2015 we conducted a survey about the knowledge and attitude of pharmacists (n = 270) using a face-to-face questionnaire. The questionnaire consisted of questions about the sociodemographic characteristics of the pharmacists, their knowledge of pharmacovigilance and their attitudes towards ADR reporting. Main outcomes measured: The majority of the pharmacists (62.6%) worked in the community pharmacies and more females responded to the questionnaire than males (59% vs 41%). only 11.9% could conceptually or actually define ‘pharmacovigilance’ correctly while one quarter of the respondent pharmacist (24.9%) could define ADR correctly. The hospital clinical pharmacists defined ‘pharmacovigilance’ correctly with higher significance (P<0.001) when compared with community pharmacists. Only 12.2% had ever reported an ADR. The majority of these reports (85%) done by the hospital pharmacists (p<0.0001). The main reasons that discourage the pharmacists from reporting ADRs were ‘‘no enough information available from the patient (76.7%)’’, and ‘‘they did not know how to report (66.7%)’’. The majority of the respondents (92.0%) felt that reporting ADR was their duty and (82%) participants were interested in participating in the National Pharmacovigilance Programme in Palestine. The results show that Palestinian pharmacists have poor knowledge about pharmacovigilance. There is an urgent need for educational programs to train them about pharmacovigilance and ADR reporting scheme.